Use of industrial hemp byproducts in ruminants: a review of the nutritional profile, animal response, constraints, and global regulatory environment - Agung Irawan; Hunter Buffington; Serkan Ates; Massimo Bionaz (Journal of Cannabis Research)
Abstract Background The legalization of industrial hemp, Cannabis sativa L., which contains < 0.3% ∆9-tetrahydrocannabinol (∆9-THC), in many countries, has led to a significant rise in its cultivation. Consequently, byproducts derived from industrial hemp processing have resulted in numerous emerging potential feed ingredients, including hempseed byproduct (HSB; hempseed cake or hempseed meal) from seed processing, hemp hurds, and hemp stalk from fiber processing, and spent hemp biomass (SHB) from cannabinoids extraction. Research to assess the potential use of these byproducts as animal feed is progressing. Method We provide an overview of the nutritional characteristics of the various hemp byproducts and provide a meta-analysis of 26 empirical studies investigating the use of hemp byproducts on ruminants. Using those studies, we delved into a comprehensive assessment regarding the effects of HSB and SHB on the health and performance of the animals. Results Overall, HSB and SHB possess excellent nutritional profiles due to their high protein content and, particularly for HSB, desirable fatty acids profile can partially replace protein-source ingredients such as soybean meal, dried distillers’ grains with soluble, canola meal, and alfalfa in the diets of ruminants. These byproducts contain diverse phytochemicals with antioxidants, anti-inflammatory, and antimicrobial properties. Data do not reveal any significant concern for the health of the animals fed hemp byproducts and, with few exceptions, the data do not indicate a substantial effect on performance; dietary inclusion of HSB, however, has a deleterious impact on rumen fermentation and nutrient digestibility when given as raw HSB without dehulling, reducing the growth performance of meat-producing ruminants. On the other hand, SHB has low palatability overall but does not impair production performance. Conclusions Although they can be promising feed ingredients for ruminants, their present use as feed ingredients is limited by the residuals of THC and CBD. Our comprehensive review of the current legal status of hemp byproducts worldwide highlighted a complex scenario with some countries allowing the use of hemp byproducts as feed ingredients, some with no clear regulations, and some countries where a path for the regulation has started, such as the US. Still, no hemp byproducts are yet legal as a feed ingredient for ruminants.